TRANSFORMING THE POST-MUWAá¸¤á¸¤IDDÅªN MAN: MALIK BENNABIâ€™S CRITIQUE OF THE CONTEMPORARY MUSLIM SOCIETY - Patria, Muhammad Yusuf (Journal of Islamic World and Politics, 2021)
This article is aimed at discussing the critical analysis of a Muslim thinker, Malik Bennabi, of the state of contemporary Muslim society. This discussion uses a descriptive-analytic approach with Bennabi's works as the primary source and other supporting works as secondary sources. Bennabi's definition of a society, especially its origin, basic elements, and its stages, is described in detail as a basis for understanding Bennabi's thoughts. then, the article discusses Bennabi's analysis and criticism of the current state of Muslim society. For him, the root of all the problems experienced by Muslim society today is an internal weakness or what he calls "colonisability". This situation, according to him, creates vulnerable individuals and societies to be "colonized" again. Bennabi referred to these individuals in Muslim society as â€œPost-Muwaá¸¥á¸¥iddÅ«n manâ€, as a sign that internal weaknesses began to emerge in Muslim society after the Muwaá¸¥á¸¥id dynasty. Based on his explanation, it can be concluded that the current Muslim society is disoriented and has lost its identity. The author also concludes that Bennabi's approach and analysis are able to describe the current state of Muslim society and the root of the problems it is experiencing.